Prodrug-based bispecific antibodies for cancer therapy: advances and future directions - Zhijuan Ai; Zhijuan Ai; Bing Wang; Yunlong Song; Panpan Cheng; Xinlin Liu; Xinlin Liu; Peng Sun (Frontiers in Immunology)
Bispecific antibodies represent an innovative paradigm in cancer therapy, offering broader therapeutic potential compared to conventional monoclonal antibodies. To increase tumor selectivity while mitigating off-target effects in normal tissues, the concept of prodrug-based bispecific antibodies has emerged. This review delineates the various mechanisms underlying the action of prodrug-based bispecific antibodies, including protease-mediated activation, steric hindrance release via proteolytic processing, activation by soluble factors, conditional assembly, and chain exchange-mediated activation. We also address the critical challenges that must be overcome to optimize the development and clinical application of these sophisticated therapeutic agents.